TUBERCULOSIS RECURRENCE AND ITS ASSOCIATED FACTORS AMONG TB REFERRAL CENTER ATTENDEES IN NEGERI SEMBILAN, MALAYSIA - Norjeehan Junadi; Raymund Dass; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Osman, Malina (Malaysian Journal of Public Health Medicine, 2025)
Tuberculosis (TB) recurrence occurs when a patient who has completed treatment is diagnosed with another TB episode. It causes continuous transmission, poor outcomes like drug resistance and non-compliance, further exhaustion of the national control budget, and reflects poor TB control programs. This study aimed to determine the incidence of TB recurrence, the mean time to TB recurrence, and its associated factors among TB patients in Negeri Sembilan. A retrospective cohort study was conducted among 422 TB patients at the Respiratory Clinic, Hospital Tuanku Ja'afar Seremban, Malaysia using secondary data from national TB Information System (TBIS) documents. Kaplan-Meier estimate was used to describe the mean time to recurrence. Cox proportional hazards models were constructed with the outcome of TB recurrence to assess whether any factors were associated with TB recurrence. Of the 422 TB patients, 32 cases were TB recurrence cases. The TB recurrence rate in Negeri Sembilan was 7.8% (95% CI 5.1-11.0). The mean time to recurrence was 170 months (95% CI 165.7-174.3). The predictors for TB recurrence were failure to gain weight over five percent (HR 2.43 95% CI 1.17-5.05), preexisting lung disease (HR 2.47, 95% CI 1.00-6.05), residents of nursing home (HR 6.56 95%CI 2.57-16.71), and non-first-line treatment regimen during maintenance phase (HR 2.80, 95%CI 1.25-6.25). By emphasizing weight gain, strict DOT/VOT for second-line treated patients, and targeted interventions for nursing home residents and those with lung comorbidities, public health initiatives can effectively contribute to the overall control and prevention of TB recurrence within communities.